치매 한약치료의 인지기능 개선 및 장내 미생물 변화에 대한 연구동향 - 최미라; Mi-ra Choi; 이정한; Jeong-han Lee; 박소현; So-hyeon Park; 김보경; Bo-kyung Kim; 임정화; Jung-hwa Lim (동의신경정신과학회지, 2023)
Objectives: This study aimed to review clinical and experimental studies using Korean traditional herbal medicine for dementia on the improvement of cognitive function and changes in gut microbiota. Methods: We searched 12 databases for clinical and experimental studies on the effect of Korean traditional herbal medicine treatment for dementia on changes in gut microbiota. Sample sizes, dementia types, diagnosis criteria, interventions, outcomes, and results, including changes in gut microbiota, were extracted from the included clinical studies and analyzed. Subjects, interventions, outcomes, and results, including gut microbiota changes, were extracted from the included experimental studies and analyzed. Results: A total of 22 studies were selected, and most of them were experimental studies. Improvement in cognitive function and changes in gut microbiota were reported in all studies. The most frequently used herbal material was Poria cocos, and the most frequently used prescription was Danggwijagyak-san and Chilseong-hwan. Lactobacillus, Firmicutes, Bacteroidetes, and Proteobacteria were frequently assessed gut microbiota. Conclusions: These results suggest the treatment potential of Korean traditional herbal medicine for dementia by regulating gut microbiota. However, there were discrepancies related to changes in gut microbiota among studies. Therefore, further studies are needed to clarify the effect and mechanism of Korean traditional herbal medicine for dementia on gut microbiota.